1996
DOI: 10.1161/01.hyp.28.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Adenylyl Cyclase/cAMP Signal Transduction and G Protein Levels in Platelets From Hypertensive Patients Improve With Antihypertensive Drug Therapy

Abstract: We have previously demonstrated a decreased expression of Gi alpha 2 protein in platelets from spontaneously hypertensive rats that was associated with an altered responsiveness of adenylyl cyclase to hormone stimulation and inhibition. In the present studies, we have used platelets from hypertensive patients and examined the hormonal regulation of adenylyl cyclase as well as the levels of G proteins and their modulation by antihypertensive drug therapy. We performed these studies in platelets from four groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…In this regard, a relationship between the levels of Gi proteins and functions has been reported by several investigators (28,(41)(42)(43). In the present studies, we have shown that the treatment of A-10 cells with C-ANP 4-23 for 24 h decreased the levels of GiR proteins by about 40%, which may partially contribute to the attenuation of C-ANP 4-23 -mediated inhibition of adenylyl cyclase.…”
Section: Discussionsupporting
confidence: 84%
“…In this regard, a relationship between the levels of Gi proteins and functions has been reported by several investigators (28,(41)(42)(43). In the present studies, we have shown that the treatment of A-10 cells with C-ANP 4-23 for 24 h decreased the levels of GiR proteins by about 40%, which may partially contribute to the attenuation of C-ANP 4-23 -mediated inhibition of adenylyl cyclase.…”
Section: Discussionsupporting
confidence: 84%
“…The inactivation of Gia-proteins by pertussis toxin [29] or the decreased expression of Gia-protein in platelets from SHR and hypertensive subjects has been shown to augment FSK-stimulated adenylyl cyclase activity [33,34]. In addition, the decreased expression of Gia-protein by C-ANP 4-23 has also been reported to augment FSK-stimulated adenylyl cyclase activity in A10 VSMC [35].…”
Section: Discussionmentioning
confidence: 99%
“…Gaq/11 proteins are involved in the regulation of the phospholipase C (PLC)/inositol phosphate (IP) signalling pathway. Accordingly, several abnormalities in receptormediated vasodilation, G-protein expression, and PLC activity, have been reported in hypertensive subjects [7,37] and in animal models of hypertension [38,39]. Recent studies have demonstrated that lipids rafts isolated from basolateral plasma membranes of rat hepatocytes were also enriched for Na ' /K ' ATPase activity [40].…”
Section: Discussionmentioning
confidence: 99%